2020
DOI: 10.3390/antibiotics9100636
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Sustainable Antimicrobial Stewardship (AMS) Programme in Ghana: Replicating the Scottish Triad Model of Information, Education and Quality Improvement

Abstract: (1) Background: Our aim was to develop robust and reliable systems for antimicrobial stewardship (AMS) in Keta Municipal Hospital and Ghana Police Hospital. Objectives were to build capacity through training staff in each hospital, establish AMS teams, collect data on antibiotic use and support local quality improvement initiatives. (2) Methods: The Scottish team visited Ghana hospitals on three occasions and the Ghanaian partners paid one visit to Scotland. Regular virtual meetings and email communication wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 9 publications
0
44
0
Order By: Relevance
“…The design quality and packaging of interventions were reported in nine studies as a facilitator, as using innovative approaches or user-friendly tools to deliver interventions improved the intervention uptake [ 38 , 49 , 51 , 53 , 57 61 ]. For example, concise guidelines that clearly outlined the appropriate antibiotics for common infections and interactive training sessions were reported to be more receptive by prescribers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design quality and packaging of interventions were reported in nine studies as a facilitator, as using innovative approaches or user-friendly tools to deliver interventions improved the intervention uptake [ 38 , 49 , 51 , 53 , 57 61 ]. For example, concise guidelines that clearly outlined the appropriate antibiotics for common infections and interactive training sessions were reported to be more receptive by prescribers.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, 12 studies found that it was difficult to promote appropriate behavior among prescribers and users in countries without national policies or guidelines for antibiotic use or those with weak enforcement of existing regulations [ 39 , 40 , 43 , 48 , 52 , 63 , 67 72 ]. In contrast, interventions that were developed in line with national AMR initiatives and the availability of national policies and guidelines facilitated the implementation of interventions to improve rational antibiotic use [ 38 , 40 , 46 , 48 , 52 , 68 , 70 , 73 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with our previous studies on antimicrobial use in the hospital. 20 , 32 , 33 , 36 , 37 …”
Section: Methodsmentioning
confidence: 99%
“…Based on initiatives from universities in cooperation with external partners, a number of point prevalence studies have been performed and/or started at: (a) KNUST Hospital (UHS), Agogo Presbyterian Hospital (APH) and Ejisu Government hospital (EGH) [40]; (b) Keta Municipal Hospital (KMH) and Ghana Police Hospital (GPH) [41]; (c) Ho Teaching Hospital [42]; (d) Point Prevalence Survey at Agogo Hospital and at St. Francis Xavier Hospital at Assin Fosu [personal information from BNITM and KCCR].…”
Section: Incomplete Implementation Of Surveillance Systemsmentioning
confidence: 99%